Taenia hydatigena cysticercosis in wild boar (Sus scrofa) from southern Italy: an epidemiological and molecular survey. Issue 14 (24th December 2020) - Sgroi, Giovanni; Varcasia, Antonio; D'Alessio, Nicola; Varuzza, Paolo; Buono, Francesco; Amoroso, Maria Grazia; Boufana, Belgees; Otranto, Domenico; Fioretti, Alessandro; Veneziano, Vincenzo
Abstract: Taenia hydatigena cysticercosis is a widespread parasitic disease of wild and domestic animals. In Europe, the increase in wild boar population may potentially contribute to the spread of this parasitic infection. To determine the occurrence of cysticerci (metacestodes) in wild boar population from southern Italy, carcasses were inspected during three hunting seasons (2016–2018). Out of 3363 wild boar examined, 229 (6.8%) harboured cysticerci with 188 (82.1%) infected by a single cyst, vs 41 (17.9%) boars having more than one. Most of the positive animals (187; 81.7%) showed cysts on the liver, whereas a multiple localization of cysticerci was reported in 10 (4.4%) wild boar. The total number of cysts retrieved from positive animals was 301 (average 1.3). Molecular analysis revealed the occurrence of a common haplotype (Hap 8) shared between wild boar and domestic animals. Our findings suggest the presence of a T. hydatigena semi-domestic life cycle in which wild boar may play an important role, due to a large number of offal available to hunting dogs, wolves and foxes during hunting seasons. Hunters may be players in the management of wildlife species to control and prevent the circulation of parasitic diseases.